UV-B RADIATION INDUCED ALTERATIONS IN THE THYLAKOID MEMBRANE LINKED PHOTOFUNCTIONS OF THE CYANOBACTERIUM SPIRULINA PLATENSIS - A. KARTHIK,; D., GUNASEKHAR,; MD. ZEEMUL HASAN,; S. D. S.MURTHY, (The Bioscan, 2011)
Depending on the illumination, UV- B radiation (2-6 w m-2) exerts multiple effects on photosynthetic electron transport. Between two photosystems, photosystem–II is highly susceptible to UV – B radiation. Light intensity measurements indicated that alterations in energy transfer from phycocyanin to Chl a is responsible for the alterations in photosystem II photochemistry of spirulina platensis. In addition UV – B radiation caused the lipid peroxidation in thylakoid membrane which could be one of the reason for the alteration in photosystem II catalyzed electron transport.